The Bee Sting That Was Not: An Unusual Case of Hymenoptera Anaphylaxis Averted in a Patient Treated with Omalizumab for Asthma - Evelyn M. Slaughter; Nathan Boyer; Steven Bennett (Case Reports in Medicine)
This paper presents a case of hymenoptera venom anaphylaxis averted by omalizumab, a monoclonal antibody to IgE antibody. This case suggests a novel and unintentional effect of this therapy. Currently omalizumab is only FDA approved for the treatment of moderate-persistent allergic asthma. However case reports, such as ours have illustrated omalizumab’s efficacy in the treatment of a myriad immunologic and allergic diseases. These outcomes have broadened the understanding of omalizumab’s complex mechanism of action.